Early Presbyterian influences at the University of Pretoria - Duncan, Graham (HTS teologiese studies, 2008)
Presbyterianism, through two significant personalities, provided an important impetus to the formation and development of the early University of Pretoria. Their contribution has to be understood in terms of the contexts of their Scottish Presbyterian heritage, South Africa in the early years of the twentieth century and the state of higher education prevalent at that time. Together these contexts may be described as political, religious and educational. Prof AC Paterson made significant contributions both in teaching and administration at the institutional level. Prof E Macmillan made his contribution in the field of teaching, but never divorced from the very context where ministry has to be exercised.